2021
DOI: 10.3390/children8030200
|View full text |Cite
|
Sign up to set email alerts
|

Level of Vocabulary Development and Selected Elements Regarding Sensory Integration and Balance in 5-Year-Old Girls and Boys

Abstract: The aim of this research was to assess relationships between the level of vocabulary and selected elements of sensory integration and balance in 5-year-old girls and boys, showing the differences between them. The study group consisted of 290 5-year-old children (172 boys and 118 girls) with different levels of vocabulary development and selected disturbances in sensory integration and balance processes. To evaluate the developmental deficits of speech with regard to vocabulary, the Children’s Dictionary Test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(15 reference statements)
0
1
0
1
Order By: Relevance
“…There was no significant correlation between the Picture Vocabulary Test–Revised scores, the OLST results, and the two-step test results in this study. A previous study of children aged 5 years reported that those with lower lexical development have more postural instability during open-eyed standing on a hard surface using stabilometry [ 26 ]. However, that study used different methods to assess static balance function and vocabulary skills from the present study, which may have impacted the differences in the results.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant correlation between the Picture Vocabulary Test–Revised scores, the OLST results, and the two-step test results in this study. A previous study of children aged 5 years reported that those with lower lexical development have more postural instability during open-eyed standing on a hard surface using stabilometry [ 26 ]. However, that study used different methods to assess static balance function and vocabulary skills from the present study, which may have impacted the differences in the results.…”
Section: Discussionmentioning
confidence: 99%
“…(2020), masalah perkembangan anak sering terjadi pada aspek keterampilan komunikasi, keterampilan afektif dan perilaku, serta otonomi. Studi Wilczyński & Ślęzak (2021), perkembangan anak laki dan anak perempuan berusia 5 tahun menunjukkan tingkat perkembangan kosa kata yang berbeda, gangguan integrasi sensorik dan proses keseimbangan. Jadi, anak yang berusia sama juga mengalami tingkat perkembangan yang berbeda.…”
Section: Pendahuluanunclassified